1968
DOI: 10.1128/aem.16.7.981-987.1968
|View full text |Cite
|
Sign up to set email alerts
|

Production of Nucleic Acid-related Substances by Fermentative Processes

Abstract: The accumulation of 5'-inosinic acid (IMP) by a mutant, KY 13102, induced from Brevibacterium ammoniagenes ATCC 6872 by ultraviolet light irradiation, was examined. Although growth was stimulated by adenine or adenosine, the microorganism showed fair growth in the medium containing amino acids but no adenine. Among six kinds of natural nutrients tested, meat extract and Casamino Acids were suitable for the accumulation of IMP. Manganese ion strongly affected growth, the accumulation of IMP and hypoxanthine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…However, further tests showed that these nucleotides were not of the 5'-isomers. Interestingly, many strains accumulated substantial amounts of adenylic acid as found by Furuya et al (1963) and Furuya et al (1964). The results reported so far show that the production of flavour enhancing nucleotides by streptomycetes seems not to be of frequent occurrence.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…However, further tests showed that these nucleotides were not of the 5'-isomers. Interestingly, many strains accumulated substantial amounts of adenylic acid as found by Furuya et al (1963) and Furuya et al (1964). The results reported so far show that the production of flavour enhancing nucleotides by streptomycetes seems not to be of frequent occurrence.…”
Section: Resultssupporting
confidence: 55%
“…Previous screening methods (Okabayashi, 1961 ;Arima et al, 1963;Nakayama et al, 1963) have usually employed the isolation of micro-organisms from various sources, their propagation in liquid media and the evaluation of UV absorbing materials prior to the specific determination of the 5'-nucleotide content. Another approach to the efficient screening for the accumulation of nucleotide-like compounds was attempted by a number of workers (Okabayashi & Masuo, 1960;E'umya et al, 1963;Furuya et al, 1964), using a purine dependent auxotroph as indicator strain.…”
Section: Tdlementioning
confidence: 99%
“…Accumulation of 5' inosinic acid (IMP) by a mutant, KY 13102, of Brevibacterium ammoniagenes was reported in our previous paper (2). During the course of our studies, manganese ion (Mn2+) was found to have striking effects on IMP accumulation at very low concentrations (10" M).…”
supporting
confidence: 57%
“…Assays. Determinations of IMP and hypoxanthine were made by a paper chromatographic method (2) with a solvent system of isobutyric acid-i N ammonia-acetic acid (10:5:1, v/v). Growth was determined by the same method as reported previously (2).…”
mentioning
confidence: 99%
“…Meanwhile, it was reported that inosine (IR) was accumulated in place of 5'inosinic acid (5'IMP) by mutants which are devoid of nucleoside degrading activity and induced from 5'IMP accumulating strain of B. ammoniagenes. 7,8) In this report, efficient conversion of 6AU to 6AUR was aimed and a suitable strain was selected from IR produc ing mutants of B. ammoniagenes. Further more, conditions for the conversion and genetical improvement of the strains was carried out, resulting in accumulation of more than 12mg of 6AUR per ml.…”
mentioning
confidence: 99%